On the approach to searching for functional dependences of data in relational systems - Filatov, V.; Doskalenko, S. (ХНУРЕ, 2018)
The subject matter of the study is information systems built on the basis of relational databases. The goal of the article is to develop a method for re-engineering relational databases that takes into account implicit interrelated functionally dependent data that affect the structure of the logical model. The following results are obtained: the approach to identify previously unknown functional dependencies based on the analysis of a set of relational database data is suggested; the classes of tasks of reengineering relational databases are specified; the stage of developing the target logic diagram which is common for the problems of adaptation and refactoring was studied; the sub-task of checking if the logic diagram of the relational database corresponds to the third normal form within this stage is considered using the synthesis method; it is shown that the solution of this task involves a number of difficulties, in particular, it is necessary to find a set of functional dependencies that are performed on the current instance of the data of a relational database; the approach for finding a set of functional dependencies from an instance of the data of a relational structure is suggested. The direction of further research can be the support of empty values at the stage of identifying functional dependencies as well as the issues of data transfer without any loss from the initial structure of the database to the target data obtained as a result of applying the methods of re-engineering. Conclusions. The approach is suggested to identify previously unknown functional dependencies which are based on the analysis of a set of relational database data. The first step is to get a set of functional dependencies for each relationship. The similar operation for the universal relation of the target database is performed at the second step. At this step, functional dependencies among the attributes of different relationships, that is the interrelationships among the data that were established during the information system operation, can be identified. The method for determining their information novelty is suggested; this method consists in verifying the membership of the functional dependencies of the universal relation while discovering the union of sets of dependencies of individual relations. A promising direction for further research is the development of methods to implement the technology for verifying if the obtained dependencies correspond to the logical model of the domain.
Keywords: reengineering; elational database; functional dependence; discovering dependences; universal relation; closing functional dependencies